(untitled) (Eurasian Medical Research Periodical, 2024)
Innovations in education refer to the use of new approaches, methods, and technologies in the field of education or the learning process with the aim of addressing existing problems and achieving more effective results. The use of various innovative teaching methods by educators contributes to the development of students’ abilities. After obtaining a diploma, education specialists develop organizational skills, clinical observations, individual psychological counseling skills, and improve their analysis and auditing skills. In the older age group, motivation to acquire new knowledge arises in situations where it is necessary to solve a problem and has practical significance.